(untitled) (Law, State and Telecommunications Review, 2025)
[Purpose] The article aims to argue, from the perspective of the right to privacy, the importance of establishing requirements for the application of electronic surveillance and the need for adequate oversight to ensure a balanced consideration of conflicting interests in the criminal process. [Methodology/approach/design] The research adopts a qualitative approach based on the study of theoretical and doctrinal foundations of the right to privacy in the digital era and electronic surveillance as an investigative act in the criminal process, to achieve a proper balance through strict compliance with the requirements for its practice. [Findings] Electronic surveillance, as a form of communication interception in the criminal process, is recognized by legal systems as one of the so-called special investigative techniques. Its use is not limited to investigating non-conventional criminality but also extends to offenses that, due to their severity and complexity, warrant it. To achieve the necessary balance between upholding the rights and guarantees of due process and limiting or restricting some of them for investigative purposes, compliance with specific requirements is essential to ensure the legality of these acts, preventing violations of fundamental rights. The doctrine establishes the principles of legality, strict necessity, and proportionality, which must guide the procedural authority responsible for authorizing and overseeing the investigative act in question. This poses a challenge following the reform of the Cuban criminal process in 2021. [Practical implications] The study establishes the right to privacy and the requirements for applying electronic surveillance in the Cuban criminal process as a theoretical framework. It also identifies the challenges faced by the Prosecutor, as the procedural authority responsible for authorizing and overseeing its application, in fulfilling the mission assigned by the 2019 Constitution of the Republic. [Originality/value] With the procedural reform introduced in Cuba through Law 143 of 2021 on the "Criminal Process," the use of special investigative techniques, including electronic surveillance as a form of communication interception, was legitimized for the first time. This is a topic with no prior studies analyzing this investigative act from the perspective of the right to privacy, the obligations regarding its impact, and potential violations, with the Prosecutor’s Office acting as its guarantor through oversight of the investigation.